Daytime sleepiness and risk of cognitive decline in dementia: a systematic review of longitudinal studies - Jânia Vanessa Morgado Silva (2021)
Objective: This study aimed to review and synthetize published studies on the longitudinal association between excessive daytime sleepiness (EDS) and cognitive decline in dementia. Methods: A comprehensive systematic search was conducted via PubMed and Scopus databases. Reference lists of included studies and grey literature were also searched. Longitudinal studies aiming to examine the impact of EDS on cognition were included. No date nor language restrictions were applied. Studies quality was assessed and a qualitative synthesis was conducted. Results: Overall, 1956 records were retrieved. From these, 4 studies fully met the eligibility criteria. These studies were published between 2002-2016, and included a total of 6874 participants, mostly diagnosed with Parkinson's disease dementia and Alzheimer's disease. Follow-up time ranged from 3-8 years, and cognition was mostly assessed with global measures. Studies revealed that patients with EDS presented significantly higher cognitive decline at follow-up, particularly older participants. Only one study revealed no significant association. Conclusions: Although these studies point towards an association between EDS and higher and faster cognitive decline, studies exploring this temporal association in dementia are still scarce. Clinical implications: Once EDS is identified, timely corrective and preventive targeted interventions can be undertaken to reduce it, potentially preventing further cognitive decline.